Perancangan dan Pengembangan Aplikasi E-commerce Pada Catering Anugrah - Siswanto Siswanto; Azwar Wardiansyah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The increasing use of the Internet by a society marked by soaring costumer and businessmen, to encourage the emergence of an internet service demand in excess of what can be obtained in the real world. This includes the opportunity to sell goods online commodity. Business people in general are still conducting business transactions manually through direct face to face or over the phone. But sometimes this method is not very effective, because not everyone knows the phone number of the company. Should be developed based E-commerce system that focuses on individual-based business transactions using the Internet (technology-based digital networks) with application of E-commerce transactions can be done more quickly and more intensively. Therefore the grace of catering company wants to advertise his wares by using websites that have a sales system based on e-commerce with the aim of selling efficiency of the way the previous sales system. The method used in the design and development of e-commerce in the catering grace Semarang is a Research and Development (R & D) in this study only up to the stage six (6) to produce the end product is a prototype, so it was not until the stage of implementation of the product. The sixth step is Research and information collecting, Planning, Develop prelminaryformof product, Preliminary field testing, revision and Main Main product field testing. The results of the research prototype applications products that have been tested in the field and meet the objectives stated in the design and application development e-commerce in the catering grace Semarang